A screening tool for psychological difficulties in children aged 6 to 36 months: cross-cultural validation in Kenya, Cambodia and Uganda - Nackers, Fabienne; Roederer, Thomas; Marquer, Caroline; Ashaba, Scholastic; Maling, Samuel; Amumpaire, Juliet Mwanga; Muny, Sothara; Sokeo, Chea; Shom, Vireak; Palha, Maria; Lefèbvre, Pauline; Kirubi, Beatrice W.; et al. (BMC Pediatrics, 2019)
Background: In low-resource settings, the lack of mental health professionals and cross-culturally validated screening instruments complicates mental health care delivery. This is especially the case for very young children. Here, we aimed to develop and cross-culturally validate a simple and rapid tool, the PSYCa 6–36, that can be administered by non-professionals to screen for psychological difficulties among children aged six to 36 months. Methods: A primary validation of the PSYCa 6–36 was conducted in Kenya (n = 319 children aged 6 to 36 months; 2014), followed by additional validations in Kenya (n = 215; 2014) Cambodia (n = 189; 2015) and Uganda (n = 182; 2016). After informed consent, trained interviewers administered the PSYCa 6–36 to caregivers participating in the study. We assessed the psychometric properties of the PSYCa 6–36 and external validity was assessed by comparing the results of the PSYCa 6–36 against a clinical global impression severity [CGIS] score rated by an independent psychologist after a structured clinical interview with each participant. Results: The PSYCa 6–36 showed satisfactory psychometric properties (Cronbach’s alpha > 0.60 in Uganda and > 0.70 in Kenya and Cambodia), temporal stability (intra-class correlation coefficient [ICC] > 0.8), and inter-rater reliability (ICC from 0.6 in Uganda to 0.8 in Kenya). Psychologists identified psychological difficulties (CGIS score > 1) in 11 children (5.1%) in Kenya, 13 children (8.7%) in Cambodia and 15 (10.5%) in Uganda, with an area under the receiver operating characteristic curve of 0.65 in Uganda and 0.80 in Kenya and Cambodia. Conclusions: The PSYCa 6–36 allowed for rapid screening of psychological difficulties among children aged 6 to 36 months among the populations studied. Use of the tool also increased awareness of children’s psychological difficulties and the importance of early recognition to prevent long-term consequences. The PSYCa 6–36 would benefit from further use and validation studies in populations with higher prevalence of psychological difficulties.
Keywords: Mental health; Psychology; Screening; Validation; Preschool children; Low-income population; Kenya; Cambodia; Uganda